Mesenchymal Stem Cells Attenuate Cisplatin-Induced Nephrotoxicity in iNOS-Dependent Manner - Bojana Simovic Markovic; Marina Gazdic; Aleksandar Arsenijevic; Nemanja Jovicic; Jovana Jeremic; Valentin Djonov; Nebojsa Arsenijevic; Miodrag L. Lukic; Vladislav Volarevic (Hindawi Limited, 2017)
Mesenchymal stem cells (MSCs) are, due to their immunomodulatory characteristics, utilized in therapy of immune-mediated diseases. We used murine model of cisplatin nephrotoxicity to explore the effects of MSCs on immune cells involved in the pathogenesis of this disease. Intraperitoneal application of MSCs significantly attenuated cisplatin nephrotoxicity, decreased inflammatory cytokines TNF-α and IL-17, and increased anti-inflammatory IL-10, IL-6, nitric oxide (NO), and kynurenine in sera of cisplatin-treated mice. MSC treatment significantly attenuated influx of leukocytes, macrophages, dendritic cells (DCs), neutrophils, CD4+ T helper (Th), and CD8+ cytotoxic T lymphocytes (CTLs) in damaged kidneys and attenuated the capacity of renal-infiltrated DCs, CD4+ Th, and CD8+ CTLs to produce TNF-α and IL-17. Similar effects were observed after intraperitoneal injection of MSC-conditioned medium (MSC-CM) indicating that MSCs exert their beneficial effects in paracrine manner. Inhibition of inducible nitric oxide synthase (iNOS) in MSC-CM resulted with increased number of TNF-α-producing DCs and IL-17-producing CTLs, decreased number of IL-10-producing tolerogenic DCs and regulatory CD4+FoxP3+ T cells, and completely diminished renoprotective effects of MSC-CM. In conclusion, MSCs, in iNOS-dependent manner, attenuated inflammation in cisplatin nephrotoxicity by reducing the influx and capacity of immune cells, particularly DCs and T lymphocytes, to produce inflammatory cytokines.